Fabrication of embedded electrodes by reverse offset printing. (23rd March 2015) - Kusaka, Yasuyuki; Koutake, Masayoshi; Ushijima, Hirobumi
Abstract: We developed a novel offset-printing process that permits the fabrication of silver-nanoparticle electrodes embedded in a dielectric layer. We succeeded in embedding approximately 1  µ m thick silver electrodes to a dielectric layer with thickness ratio of 1:1.4. The surface-height difference between the embedded electrode and the surrounded dielectric layer was less than 80 nm. By virtue of the surface uniformity of this embedding process, the interconnect breakage of orthogonal wires printed on top of the underlying wire was drastically reduced to 4%, compared to 41% for non-embedded wires. The electric conductivity of embedded electrodes with thickness ≈110 nm was about 10 µΩ cm −1, which was comparable to that of a silver pattern formed on a glass substrate alone. We also examined the characteristics of fully printed thin-film transistors composed of the embedded electrodes, and measured an average mobility of 0.07 cm 2  V −1 s −1 . These results demonstrate the applicability of the proposed technique to the fabrication of printed circuits and devices including active elements.